2020
DOI: 10.14198/jhse.2022.171.15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of corner kicks in FIFA 2018 World Cup

Abstract: The aim of this study is to analyse the corner kicks taken in the matches played in the FIFA 2018 World Cup. A total of 606 corner kicks that were used in 64 matches in the competitions were analysed. The data were analysed in terms of the parameters of the direction in which the corner kick is taken (right, left), the time interval in which the corner kick is taken (1-15, 16-30, 31-45, 46-60, 61-75, 76-90), the region where the ball falls in the penalty area (1 st , 2 nd , 3 rd , 4 th , 5 th , 6 th .), the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…However, when set play is used, it is easier to shoot the ball because it remains stationary on the ground, opposing players must remain at some distance from the ball, and the attacking team can choose the moment to start the action. Being close to the opponent’s goal enables sending the ball into the penalty box with the immediate intention to score a goal and more players can be positioned in front of the opposing goal ( Zileli and Söyler, 2020 ). All of the aforementioned characteristics could influence training plans to devote more time to set play (both attacking and defending), particularly in the few weeks that national teams have to prepare for a major tournament.…”
Section: Discussionmentioning
confidence: 99%
“…However, when set play is used, it is easier to shoot the ball because it remains stationary on the ground, opposing players must remain at some distance from the ball, and the attacking team can choose the moment to start the action. Being close to the opponent’s goal enables sending the ball into the penalty box with the immediate intention to score a goal and more players can be positioned in front of the opposing goal ( Zileli and Söyler, 2020 ). All of the aforementioned characteristics could influence training plans to devote more time to set play (both attacking and defending), particularly in the few weeks that national teams have to prepare for a major tournament.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a variety of reasons for making substitutions, such as modifying tactical behaviours [ 22 ], counteracting fatigue [ 23 ], restructuring the team after a player has been dismissed, replacing yellow carded players [ 24 ], replacing injured or underperforming players [ 25 ] as well as providing playing time to players with fewer minutes and preventing fatigue accumulation among other team members [ 26 ]. Substitutes are typically introduced at halftime or during the second half of the game [ 25 , 26 ], although the differences in physical performance have not been studied using time criteria [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Relationship between Shot on Goal Level and the Final Results of Soccer Matches in the 2021 Indonesian League 3 Bali Zone and anthropometric research [4]. Match analysis is an objective record and analysis of behavior that occurs during a match or competition [5]. The main purpose of the match analysis process is analyzing the weaknesses and strengths of the opposing team and our own team [6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above review, in fact many previous researchers have revealed the performance of soccer at the elite or professional level namely, the playing style of a team when attacking and defending was analyzed [14], physical and technical performance in each different playing position in the English Premier League [15], identification of scoring opportunities and offensive and defensive strategies as indicators that can be distinguished between teams winning or losing matches in the 2012 European Soccer Championship [16], percentage of ball possession and successful passing of teams that were successful in 2014 FIFA World Cup [17], technical performance profiles of the teams involved in the 2016 European Soccer Championship [3], described how scoring opportunities arise and chances were executed in Major League Soccer by considering indicators of offensive and defensive tactics [18], measuring guard performance goal in all matches at EURO 2016 [19], the level of centrality between playing positions in the national team that played in the 2014 FIFA World Cup [20], analysis of goalkeeper performance related to the role in the game [21], competitive profile of the best leagues in Europe such as the Spanish League, Italian League, English League, Germany League, Portuguese and French Leagues [22], the characteristics of the sequence of attacks in soccer that are most effective on the opponent's defensive area, and the distance between the defensive line and the goal [23], the situation of the game from the recovery of the ball to the goals scored by professional soccer players. men's and women's League 1 Portugal [24], identification of technical and tactical action at each player position during play in the Ukraina Premier League [25], characteristics of goal scoring passing networks during the 2016 European Soccer Championships [26], influence of small-sided games on the game performance of young soccer players [27], observation of the motor activities of Greece professional soccer players on this during one competitive season [28], analysis of the quality of the team in the ball recovery which is influenced by the quality of the opponent, the quality of the field and the status of the match [7], shooting characteristics and goal scoring in the 2019 Women World Cup Soccer Tournament [29], analysis of the goal process scored during Euro 2020 [30], and analysis of corner kicks during the 2018 FIFA World Cup [5].…”
Section: Introductionmentioning
confidence: 99%